Ableism and the Infrahumanisation of ?Others? - Bełza, Magdalena (INSTED: Interdisciplinary Studies in Education & Society, 2016)
The purpose of this article is to draw attention to the infrahumanisation phenomenon of Otherness in the context of ableism. In the discussion, a reference is made to the concept of infrahumanisation, explaining what its essence and characteristic features are; ableism which is the discrimination form directed towards people with disabilities, attitudes (considering their three-dimensionality) and five forms of discrimination proposed by Stanislaw Kowalik?s classification. Both attitudes and individual forms of discrimination have been examined through the prism of infrahumanisation showing its close relationship and the prevailing relations between these issues.